2012
DOI: 10.1038/mi.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of MyD88 in intestinal epithelial cells results in compromised antibacterial immunity associated with downregulation of polymeric immunoglobulin receptor, mucin-2, and antibacterial peptides

Abstract: Intestinal epithelial cells (IECs) form a physical and immunological barrier that separates the vast gut microbiota from host tissues. MyD88-dependent Toll-like receptor signaling is a key mediator of microbial–host cross-talk. We examined the role of epithelial MyD88 expression by generating mice with an IEC-targeted deletion of the Myd88 gene (MyD88ΔIEC). Loss of epithelial MyD88 signaling resulted in increased numbers of mucus-associated bacteria; translocation of bacteria, including the opportunistic patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 58 publications
3
153
4
1
Order By: Relevance
“…Freshly collected feces were weighed, homogenized in ELISA buffer [50 mM Tris (pH 7.4), 0.14 M NaCl, 1% BSA, and 0.05% Tween 20] and stored at −20°C until analysis. IgA was quantified by ELISA as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Freshly collected feces were weighed, homogenized in ELISA buffer [50 mM Tris (pH 7.4), 0.14 M NaCl, 1% BSA, and 0.05% Tween 20] and stored at −20°C until analysis. IgA was quantified by ELISA as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…The host transcriptome data set of Larsson et al (2011), which uses both GF (discussed below) and MyD88-sufficient and -deficient conventional mice, is available as a community-wide resource at Encyclopedia of Tut Microbiota Regulated Genes (http://microbiota.wall.gu.se). Targeted intestinal epithelial deletion of MyD88 using Villin-Cre 3 MyD88-Flox mice has revealed that such mice have reduced levels of the polymeric immunoglobulin receptor mucin-2 and antibacterial peptides (Frantz et al 2012). MyD88 regulation of the expression of RegIIIg, an antibacterial lectin that lyses Gram-positive bacteria, is of special importance, as RegIIIg restricts the localization of bacteria and ensures its proper segregation from the inner mucus layer of the intestinal mucosa (Vaishnava et al 2011).…”
Section: Micementioning
confidence: 99%
“…In addition to reduced chemokine expression as seen in this study, Frantz et al 38 recently reported a reduced pIgR mRNA expression in Myd88 IEC−/− mice compared with Myd88 f/f mice, leading to a decrease in levels of luminal sIgA. Mucosal antibodies have the potential to recognize "neoantigens" revealed on ischemic cells and to activate the complement pathway, leading to exacerbate damage during I/R-induced injury.…”
Section: Discussionmentioning
confidence: 95%